KANDUNGAN TOTAL SUSPENDED SOLID DAN SEDIMEN DI DASAR DI PERAIRAN PANIMBANG - Helfinalis, Helfinalis (Makara Journal of Science, 2005)
Total Suspended Solid Content And Sediment On The Bottom Surface Of Panimbang Water. The study of dynamics oceanography have been executed on June 2004 in the East season. Distribution of total suspended solid on the surface and bottom waters at the Estuary of Ciliman River is lower than Estuary of Cibungur River. Generally mud and silty mud of sediment on the bottom surface waters covered the western part of Panimbang beach. Gravel, silty sand and muddy sand with forams, fraction of mollust and corals found at the Southwest of the study area. In that area is also found many floating of Bagan Apung which is assumed as rich with fishes